2017
DOI: 10.13044/j.sdewes.d5.0156
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Electricity Generation from a Large System of Wind Plants and Demand for Fast Regulation

Abstract: Experimental data of total wind generation, recorded at 5 minute intervals and published by the Bonneville Power Administration for the years 2007 to 2013, were analyzed on a year by year basis. All data were normalized to total installed power of wind plants. Statistical distribution functions were obtained for the following wind generation-related quantities: total generation as percentage of total installed capacity; change in total generation power in 5,10,15,20,25, 30, 45, and 60 minutes as percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is a well-known problem. For example, after studying the seven-year stream of 5-minute readings of the energy output from an extensive system of wind plants in the north-western USA, the authors of [16] found out that the demand for fast regulation can be expressed as:…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a well-known problem. For example, after studying the seven-year stream of 5-minute readings of the energy output from an extensive system of wind plants in the north-western USA, the authors of [16] found out that the demand for fast regulation can be expressed as:…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…Fig. 10, taken from [16], gives the results of the experimentally derived MReg for the above-mentioned American wind plant system in the whole of the year 2013, together with the curve (2) fitted to the data using the least squares. For example, according to Fig.…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The next question to address, as it comes to application of portfolio optimisation theory to wind plants, pertains to the fact that distributions of energy produced by a system of wind plants are notoriously non-Gaussian (Sabolić [18]). Markowitz's theory, on the other hand, relies on an assumption of normal distribution of data.…”
Section: How Non-gaussian Nature Of Wind Generation Affects Optimisation?mentioning
confidence: 99%
“…The second major objection on Markowitz's theory pertains to assumption of Gaussian distribution of observed data population. There is a lot of evidence that wind production is not at all Gaussian (see for example Sabolić [18]). In Monahan et al [19] probability density function of land surface wind speeds is characterized using a global network of observations, to conclude that it is essentially a Weibull distribution, which is skewed (non-symmetric about expected value).…”
Section: Introductionmentioning
confidence: 99%